The Impact of Public Open Space on the Image of Small Towns Centres in Slovenia (Prostor, 2023)
Despite all the principles of sustainable urban design, more and more spaces in small town centres are getting dedicated to traffic. Public open spaces (POS) in these towns are mainly reserved for car traffic, and social activities have been in decline. All at the expense of transportation space and built-up areas. As a result, there are fewer and fewer POS, which provide well-being and comfort to people, are accessible to all and are also attractively designed, allowing the development of a wide range of activities, and contributing to a town’s good image. Therefore, the aim of this paper is to determine the state of provision of POS in the centres of selected small towns in Slovenia and to assess the image of these town centres. Using various methods and instruments, we tested the hypothesis of whether there is a relationship between POS and the image of town centres. We used a cartographic method and a questionnaire survey, as well as statistical methods, in order to confirm the hypothesis. The study has revealed that groups of morphologically similar small towns are statistically different from each other in terms of observed relationships between POS and the image of the town centre. Therefore, a morphological analysis approach is very important in terms of evaluating the relationship between POS and the image of town centres. In conclusion, recommendations are given for the design of POS in small town centres.